Alat Deteksi Persentase Penyusutan Kadar Air Pada Sample Rumput Laut Berbasis Air Fryer Yang Dimodifikasi - Safriudin Rifandi; Bagus Kusuma Aditya; Nuhman Nuhman; Muh. Taufiqurrohman; Suryadhi Suryadhi; Joko Subur; Tri Agung Kristiyono; Nurul Rosana; Indra Widyadharma (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
Abstract - Seaweed is one of the biological resources that is very abundant in Indonesian waters. Indonesia's seaweed export products are currently still dominated by seaweed products, reaching 80%. For export needs, the water content of seaweed must reach around 15%. To achieve export standard moisture content, wholesalers or industries usually carry out the seaweed drying process independently. Meanwhile, to avoid losses in exporting dried seaweed, they test seaweed samples to be purchased to determine the percentage of water content reduction in the seaweed. In the testing process, currently we are still using a small oven with a gas-burning stove and a separate digital scale. The use of this device is felt to be less effective and less flexible in its application. Therefore, we need a tool that is integrated into one and is small in size to detect the percentage of water content reduction in seaweed samples. In this research, experimental methods were used in testing equipment and collecting data. The results of the experiment showed that a good temperature to use in drying seaweed samples was 160 OC with the result that the seaweed was dry but not burnt. Meanwhile, the shrinkage percentage is around 34.72%.